2015
DOI: 10.1002/pi.4922
|View full text |Cite
|
Sign up to set email alerts
|

Metal complexation studies of amylopectin‐graft‐poly[(N,N‐dimethylacrylamide)‐co‐(acrylic acid)]: a biodegradable synthetic graft copolymer

Abstract: Synthesis of amylopectin‐graft‐poly[(N,N‐dimethylacrylamide)‐co‐(acrylic acid)] was carried out using solution polymerization technique with potassium persulfate as the initiator. The graft copolymer was characterized by measuring molecular weight using size exclusion chromatography, thermal analysis and Fourier transform infrared (FTIR) spectroscopy. The synthetic graft copolymer was used for the removal of some potentially toxic metal ions, Cu(II), Zn(II) and Ni(II), from their aqueous solutions. Various ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…And the complexation was substantiated by the position reduction of −COO – peaks from ∼1718 to ∼1667.2 cm –1 (Figure S3B). Thus, Ga 3+ ions would serve as cross-linkers to reinforce the organic shells, in analogy to our previous report . And the surface oxidation should benefit the coating of the polymeric shells …”
Section: Results and Discussionsupporting
confidence: 64%
“…And the complexation was substantiated by the position reduction of −COO – peaks from ∼1718 to ∼1667.2 cm –1 (Figure S3B). Thus, Ga 3+ ions would serve as cross-linkers to reinforce the organic shells, in analogy to our previous report . And the surface oxidation should benefit the coating of the polymeric shells …”
Section: Results and Discussionsupporting
confidence: 64%
“…The UV–vis spectra of the Hg(II)‐loaded SKG‐ g ‐PNVI and Hg(NO 3 ) 2 salt solution in water (SKG‐ g ‐PNVI) showed that it was sparingly soluble in hot water. We obtained the medium for the UV–vis spectral analysis by heating a very small amount of sulfated polymer in an excess amount of water at 80 °C for 4 days and then filtering it, as shown in Figure (c). We observed from the figure that Hg(II) absorbed at 298 nm, but when Hg(II) was complexed with O SO3, a redshift occurred [maximum wavelength (λ max ) = 368.5 nm, as shown in the inset in Figure (c)].…”
Section: Resultsmentioning
confidence: 99%
“…Adsorption is a widely used process worldwide for the removal of chemical contaminants from water. It is favored among various water treatment methods due to its simplicity and excellent ability to remove metal ions [138,139] and dye molecules in water [140,141]. Unlike other processes, adsorption is sludge-less and can be effective for both high and low concentrations of pollutants.…”
Section: Adsorptionmentioning
confidence: 99%
“…The concentration of glucose can be determined by measuring the optical density (OD) using a photoelectric colorimeter after adding DNS (2,4-dinitrosalicylic acid) at pH 6.7 in a phosphate-buffered solution (PBS) [216]. The results of the study are summarized in Figure 10a [120,139,181,216]. The polysaccharides exhibited a more rapid degradation compared to the graft copolymers.…”
Section: Biodegradation Of Polymeric Materialsmentioning
confidence: 99%
See 1 more Smart Citation